Effect of Soil Tillage and Adaptability of Argomulyo and Burangrang Varieties in Madagascar Dry Season with Cold Temperature - Heru Kuswantoro; Sudaryono Sudaryono; Suharsono Suharsono; Yudi Widodo; Yusral Tahir; Widyanto Soetajan; Mesah Tarigan; Ade Candradijaya (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2017)
This research aimed to study soybean response to different soil tillage and soybean adaptability to dry season with cold temperature. Two Indonesian varieties (‘Argomulyo’ and ‘Burangrang’) and three Madagascar varieties (‘FT10’, ‘OC11’ and ‘Malady’) were grown under soil tillage and no soil tillage in Antananarivo Avarandrano, Madagascar. The planting date was from June to November 2014 in which the season was dry season with average temperature ranging 14-19 oC. Results showed that there was no variety × tillage interaction on the observed characters. Tillage system was significantly different on plant height, number of pods plant-1, grain size, and grain yield. The differences among varieties were found on vegetative and generative phases, plant height, number of branches and pods plant-1, grain size, and grain yield. Cold temperature suppressed growth and development of vegetative and generative phases causing agronomical characters decreased. However, soybean plants were still able to grow and develop indicating that soybean can be grown under no tillage system with cold temperature. Indonesian varieties (‘Argomulyo’ and ‘Burangrang’) showed equal grain yield to Madagascar Varieties (‘FT10’ and ‘OC11’), suggesting that ‘Argomulyo’ and ‘Burangrang’ were adaptable in Madagascar dry season with cold temperature.